First morphological and molecular identification of mealybug Cadra cautella (Lepidoptera: Pyralidae) in Karbala, Iraq - Al-Khalidi, Noor; Al-Zurfi, Sienaa Muslim (Journal of Kerbala for Agricultural Sciences, 2025)
Cadra cautella (Walker, 1863) (Lepidoptera: Pyralidae) is a significant pest insect of dried products that has become widespread in storge products of Karbala Province. Integrating molecular data using Next Generation sequencing alongside morphological data from a comprehensive collection of live specimens was applied to identify C. cautella in Karbala, Iraq. The morphemic identification of the almond moth common in Karbala is C. cautella. This identification was confirmed molecularly. In addition, this insect's mitochondrial genes mtCOX1 were recorded in GenBank with accession numbers PP916775 and PP921921, with 657 and 651 bp long, respectively Another two genes of this insect were sequenced successfully: the hydroxymethylglutaryl-CoA lyase and vitellogenin genes deposited in GenBank under accession numbers PP928485 and PP928484. The results showed that for the first time, the identification of C. cautella and its genes was reported based on molecular biology in Karbala, Iraq. The research results help identify and distinguish the almond moth species using NGS and are beneficial for the better choice and application of control strategies against it.